Efficient Heterogeneous Palladium‐Catalyzed Oxidative Cascade Reactions of Enallenols to Furan and Oxaborole Derivatives. (13th December 2019) - Li, Man‐Bo; Posevins, Daniels; Geoffroy, Antoine; Zhu, Can; Bäckvall, Jan‐E.
Abstract: A heterogeneous palladium‐catalyzed oxidative cyclization of enallenols has been developed for the construction of highly substituted furan and oxaborole derivatives. The heterogeneous catalyst (Pd‐AmP‐MCF) exhibits high activity, high site‐ and stereoselectivity, and efficient palladium recyclability in the transformations. Abstract : Heterogener Ligand : Eine hocheffiziente heterogene, palladiumkatalysierte oxidative Cyclisierung von Enallenolen für den Aufbau hochsubstituierter Furan‐ und Oxaborolderivate wurde entwickelt. Der Träger (AmP‐MCF) des heterogenen Katalysators (Pd‐AmP‐MCF) schützt die Pd‐Spezies vor der Aggregation zu Pd black während des katalytischen Zyklus, was zu der hohen Pd‐Effizienz von Pd‐AmP‐MCF führt.